Phonological acquisition in children aged 2;2 (psycholinguistic study) - Eva Fitrianti; Yefrizon Yefrizon (Universitas Asahan, 2025)
Language acquisition in early childhood is a natural and systematic process that reflects a child's cognitive and linguistic development. This study aims to describe the phonological acquisition of Indonesian vowel sounds by a 2-year-2-month-old child, focusing on the production of the five primary vowels /a/, /i/, /u/, /e/, and /o/ in initial, medial, and final word positions. Employing a qualitative descriptive method, data were collected through observation and note-taking of spontaneous utterances in natural communication contexts. The findings reveal that the child had successfully acquired all five vowel phonemes, with dominant mastery of /a/, /i/, and /u/. The phonological acquisition process was characterized by simplification strategies, including omission, substitution, and assimilation. These strategies indicate that the child adapted to articulatory limitations by restructuring complex phonemes into simpler ones. The consistent use of vowel sounds demonstrates a universal pattern of phonological development influenced by both internal (physiological maturity) and external (linguistic environment) factors. This study contributes to psycholinguistic research and offers practical insight for educators and parents in supporting early language development and identifying potential language delays.